Assessment of Reporting Quality in Randomised Controlled Trials of Acupuncture for Post-Stroke Rehabilitation Using the Consort Statement and Stricta Guidelines. Issue 2 (April 2017) - Zeng, Jingchun; Lin, Guohua; Li, Lixia; Lu, Liming; Chen, Chuyun; Lu, Lihong
Objectives: To evaluate the completeness of reporting of randomised controlled trials (RCTs) of acupuncture for post-stroke rehabilitation in order to provide information to facilitate transparent and more complete reporting of acupuncture RCTs in this field. Methods: Multiple databases were searched from their inception through September 2015. Quality of reporting for included papers was assessed against a subset of criteria adapted from the Consolidated Standards for Reporting Trials (CONSORT) 2010 statement and the Standards for Reporting Interventions in Controlled Trials of Acupuncture (STRICTA) guidelines. Each item was scored 1 if it was reported, or 0 if it was not clearly stated. Descriptive statistical analysis was performed. Cohen's κ-statistics were calculated to assess agreement between the two reviewers. Results: A total of 87 RCTs were included in the full text. Based on CONSORT, good reporting was evident for items "Randomised' in the title or abstract', 'Participants', 'Statistical methods', 'Recruitment', 'Baseline data', and 'Outcomes and estimation', with positive rates >80%. However, the quality of reporting for the items 'Trial design', 'Outcomes', 'Sample size', 'Allocation concealment', 'Implementation', 'Blinding', 'Flow chart', 'Intent-to-treat analysis', and 'Ancillary analyses' was very poor with positive rates <10%. Based on STRICTA, the items 'Number of needle insertions per subject per session', 'Responses sought', and 'Needle type' had poor reporting with positive rates <50%. Substantial agreement was observed for most items and good agreement was observed for some items. Conclusions: The reporting quality of RCTs in acupuncture for post-stroke rehabilitation is unsatisfactory and needs improvement.